Framework for location based attendance system by using fourth industrial revolution (4ir) technologies - Ali, Azhar; Koondhar, Muhammad; Depar, Mansoor Hyder; Maher, Zulfikar Ahmed; Rind, Muhammad Malook; Shah, Asadullah (World Academy of Research in Science and Engineering, 2021)
Information Technology (IT) is an emerging field that plays a significant role in every field of today’s world. In the education systems, IT has replaced many traditional methods with trending digital technologies and solved the problems and hurdles that usually occur. Besides these, IT is a key factor that is responsible for digitization and automation that ultimately have led us to the 4th industrial revolution (4IR), which is an upgrade of the previous 3 industrial revolutions. The 4IR is not only for industrial production, but it is also involved in almost every field including education and commercial domains. In every organization, including an educational institute or any other commercial organization, attendance has a great importance. In the recent past, several IT technologies have been used to replace the traditional paper-based attendance method with digital attendance mode, for that purpose, there have been several techniques in use since long time i.e. Near Field Communication; NFC, Radio Frequency Identification; RFID, Biometric, Quick Response Code; QR-Code, etc. Though, these types of techniques were very efficient but had some flaws such as risks of prone attendance, the queue of a crowd waiting in front of attendance device, high time consuming etc. This research was planned to overcome these issues by introducing a new approach by designing a framework for location-based attendance system using digital technologies of the 4IR. The designed framework was based on BYOD (Bring Your Own Device) trend, in which students rather than teachers can mark their attendance using their own devices. This framework was a 3 layered framework i.e. client layer, data synchronization layer, and server layer. The framework was validated by developing a system and testing it at the Information Technology Centre, Sindh Agriculture University Tandojam, Pakistan. For calculating the empirical results, an evaluation was performed. The designed framework proved to be more secure, all the data in the framework was encrypted with a strong encryption algorithm, final attendance of successful students was stored in the blockchain structure to maintain the confidentiality and integrity in data. The designed framework used triple authentication i.e. biometric authentication, QR-code authentication, and location based authentication that reduced the risk of prone attendance.